Hybrid Mass Spectrometry Approaches to Determine How L-Histidine Feedback Regulates the Enzyzme MtATP-Phosphoribosyltransferase - Pacholarz,KJ; Burnley,RJ; Jowitt,TA; Ordsmith,V; Pisco,JP; Porrini,M; Larrouy-Maumus,G; Garlish,RA; Taylor,RJ; de,Carvalho LPS; Barran,PE (Structure, 2017)
MtATP-phosphoribosyltransferase (MtATP-PRT) is an enzyme catalyzing the first step of the biosynthesis of L-histidine in Mycobacterium tuberculosis, and proposed to be regulated via an allosteric mechanism. Native mass spectrometry (MS) reveals MtATP-PRT to exist as a hexamer. Conformational changes induced by L-histidine binding and the influence of buffer pH are determined with ion mobility MS, hydrogen deuterium exchange (HDX) MS, and analytical ultracentrifugation. The experimental collision cross-section (DTCCSHe) decreases from 76.6 to 73.5 nm2 upon ligand binding at pH 6.8, which correlates to the decrease in CCS calculated from crystal structures. No such changes in conformation were found at pH 9.0. Further detail on the regions that exhibit conformational change on L-histidine binding is obtained with HDX-MS experiments. On incubation with L-histidine, rapid changes are observed within domain III, and around the active site at longer times, indicating an allosteric effect.